Practical synthetic strategies towards lipophilic 6-iodotetrahydroquinolines and -dihydroquinolines - Chisholm, David R.; Zhou, Garr-Layy; Pohl, Ehmke; Valentine, Roy; Whiting, Andrew (Beilstein Journal of Organic Chemistry, 2016)
The synthesis of novel tetrahydroquinolines (THQ) and dihydroquinolines (DHQ) are reported using three practical, scalable synthetic approaches to access highly lipophilic analogues bearing a 6-iodo substituent, each with a different means of cyclisation. A versatile and stable quinolin-2-one intermediate was identified, which could be reduced to the corresponding THQ with borane reagents, or to the DHQ with diisobutylaluminium hydride via a novel elimination that is more favourable at higher temperatures. Coupling these strongly electron-donating scaffolds to electron-accepting moieties caused the resulting structures to exhibit strong fluorescence.
Keywords: cyclisation; dihydroquinoline; elimination; reduction; tetrahydroquinoline